Poetry Musicalization as an Integrative Learning Model: Linguistic, Musical, and Character Collaboration in Secondary Education - Burhanudin, Muhamad; Zustiyantoro, Dhoni; Nur Rokhim, Mukhammad; Kurniasih, Yacinta; Nuryatin, Agus; Supriyanto, Teguh (Universitas Negeri Semarang, 2025)
Poetry musicalization represents a creative synthesis of literary and musical arts that can enrich language and arts learning in secondary schools. This study analyzes the creative process of poetry musicalization as an intermedial adaptation and examines its pedagogical value for developing students’ linguistic, musical, and character competencies. Using a qualitative phenomenological approach, data were collected through in-depth interviews with ten Indonesian and Javanese language teachers at SMA and SMK in Central Java, supported by document analysis and observations of musicalized versions of Sapardi Djoko Damono’s Hujan Bulan Juni and Goenawan Mohamad’s Z on YouTube. The findings reveal that the musicalization process involves poem selection, semantic interpretation, melodic and rhythmic composition, arrangement, and audio-visual realization. Classroom implementation requires active collaboration between teachers and students and contributes to improved language proficiency, artistic appreciation, creativity, and self-confidence. In conclusion, poetry musicalization has strong potential as an integrative learning method that balances cognitive and affective domains, promotes contextual and meaningful learning, and supports interdisciplinary classroom practices.